2008
DOI: 10.1080/09602010701406581
|View full text |Cite
|
Sign up to set email alerts
|

New learning in dementia: Transfer and spontaneous use of learning in everyday life functioning. Two case studies

Abstract: The purpose of these two case studies was to explore the effectiveness of learning methods in dementia when applied in real-life settings and the integration of new skills in daily life functioning. The first participant, DD, learned to look at a calendar with the spaced retrieval method to answer his repeated questions about the current date and calls made to family. Progressive cuing was used by his wife to increase spontaneous use of the calendar, but DD had difficulty integrating the calendar into his rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Most studies focused on teaching participants the use of devices such as a mobile phone, answering machine, coffee maker, or microwave 28,31,33,34,36,41. Participants also practiced face-name associations of familiar people, such as family members or members of a social club,27,29,34,35 and orientation skills,28,30,34 such as the use of a calendar and directions (routes).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies focused on teaching participants the use of devices such as a mobile phone, answering machine, coffee maker, or microwave 28,31,33,34,36,41. Participants also practiced face-name associations of familiar people, such as family members or members of a social club,27,29,34,35 and orientation skills,28,30,34 such as the use of a calendar and directions (routes).…”
Section: Resultsmentioning
confidence: 99%
“…Participants also practiced face-name associations of familiar people, such as family members or members of a social club,27,29,34,35 and orientation skills,28,30,34 such as the use of a calendar and directions (routes). Relearning the names of everyday objects was practiced in six studies 32,3840.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, some authors had already reported the effi cacy of some learning methods in individualized cognitive training programs for AD. However these effi cacy data were based only on a few studies (Adam et al 2000;Lekeu et al 2000;Clare et al 2001;Bier et al 2008). Therefore, the principal goal of the present study was to assess the preliminary effi cacy of an individualized cognitive training program using the EL and SR techniques to relearn forgotten IADLs in mild AD.…”
Section: Thivierge Et Almentioning
confidence: 95%